Pelatihan Keterampilan Motorik Dan Kontribusinya Terhadap Pencapaian Hasil Belajar Siswa - Jamil, Sofyan; Muhammad , Heryanto Nur; Priambodo, Anung; Ardha, Muchamad Arif Al (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
Education aims to optimally develop students' cognitive, affective, and psychomotor potential. In physical education, motor skills are a crucial aspect that affects students' concentration, coordination, and stamina in learning. This quantitative study with a correlational design aims to determine the contribution of motor skills to student learning outcomes. The data were analysed using simple linear regression tests. The results showed a significant relationship between motor skills and academic achievement, as evidenced by a significance value of < 0.05. Thus, the alternative hypothesis (H_1) was accepted and the null hypothesis (H_0) was rejected. The findings showed that motor skills contributed 59.5% to student learning outcomes, while the remaining 40.5% was influenced by other variables. This study confirms that strengthening psychomotor skills is a key factor in accelerating students' academic performance at school.